(untitled) (Al-Quds Journal for Natural Sciences, 2021)
Enteropiasis is a parasitic disease caused by the pinworm; Enterobius vermicularis. In this report, the prevalence of Enterobius vermicularis infection in the West Bank and Gaza strip was investigated based on Palestinian Ministry of Health reports from 2008 to 2018. A total of 29,390 cases was reported, 29,061 (98.9%) in the West Bank, and 329 cases (1.1%) in Gaza Strip. The results of the present study show that E. vermicularis infection is highly prevalent among people living in the West Bank and to lesser extend in Gaza Strip. There is a need for joint and concentrated e"orts from the Palestinian government and public health services to control this infection. Personal hygiene, education and living conditions and overcrowding are risk factors associated with the spread of infection.